WUJUD VISUAL GAMBAR - ILUSTRASI PADA NASKAH NASKAH TUA NUSANTARA SEBAGAI REFLEKSI INTELEKTUALITAS LELUHUR BANGSA INDONESIA - Nuning Y. Damayanti Adisasmito (LP2M ISBI Bandung, 2012)
Manuscript is a cultural product belongs to every civilized community that understands letters and words. Visual communication, before script and writing were established, such as ancient drawings, has been used by people since thousands years ago. The discovery of picture in prehistoric caves is considered as the beginning of drawing tradition towards the modern illustration. The discovery of scripts and writing shifted the tradition of drawing, although the simplest and the most effective communication is still the visual language. It explains why an illustrative drawing in the old manuscript was used as a communication device which reflects the cultural development and the way of thinking from the society who created it. The tradition of writing and drawing in illustration was found in the Javanese and Balinese old manuscripts. The visual illustration, theme, and media of manuscripts shown similar in diversity, depend on their role in social life. Some parts of those old manuscripts show unique illustrations as well as the local identity of the society. The illustration on manuscript reflects the society culture of thinking and aesthetic achievement of visual art. Key Words: Illustration, old Indonesian manuscript, visual language.